PENGARUH ELEMEN BIOPHILIC DALAM LINGKUNGAN RUANG TERHADAP RESPONS PSIKOLOGIS DAN FISIOLOGIS PENGGUNA: TINJAUAN LITERATUR SISTEMATIS - Tjokorda Istri Sukma Pramudawardani; Andriyanto Wibisono; Etika Vidyarini (Jurnal Arsitektur ARCADE, 2026)
Modern lifestyles require people to spend long periods in enclosed environments under high cognitive demands, leading to mental fatigue, reduced concentration, and prolonged stress. Biophilic design integrates natural elements into built environments to improve wellbeing. However, many studies evaluating biophilic design still rely on subjective perception questionnaires that are prone to bias. This Systematic Literature Review aims to clarify research protocols and map the influence of biophilic elements on physiological responses. Using PRISMA guidelines, literature was collected from Scopus, PubMed, and Google Scholar for the period 2015 – 2026. A total of 20 empirical studies measuring physiological responses using instruments such as HRV, EEG, and Eye - Tracking were analyzed. Results show that vegetation accelerates autonomic nervous system recovery through HRV metrics, while biomimetic patterns help restore brain wave activity. Validity depends on experimental protocols, with ideal exposure durations of 5-15 minutes. In Virtual Reality (VR) simulations, exposure should be limited to prevent virtual sickness that may distort data (3–5 minutes). Pre-stressor tasks are also required to evaluate stress recovery. In conclusion, Biophilic design functions as a measurable, evidence-based approach for restorative environments. Keywords: Biophilic design, Physiological Response, Systematic Literature Review.